(untitled) (Research, Society and Development, 2021)
This work aimed to characterize certified organic farmers in the municipality of Marechal Cândido Rondon – PR. Qualitative and quantitative research, analytically structured on data obtained from the 2017 Agricultural Census, the Brazilian Institute of Geography and Statistics (IBGE), and the National Register of Organic Producers, in addition to a bibliographic survey on production, food and organic certification. The study revealed that from the universe of 1,934 agricultural establishments in the municipality, only 47 (2.4%) use the organic production system, whose certification is carried out by the Ecovida Participative Certification Association, Paraná Institute of Technology and Ecocert Brasil Certificadora. It was observed that 33 establishments are owned by family farmers and 14 non-family production units, where production is articulated only in crops (35) or creations (5) and mixed systems (7), in properties whose area varies by approximately from 0.5 to 20 hectares, and 35 properties are managed by men and 12 farms by women. The study concludes that, despite the limited quantitative expression of organic farmers in the municipality, the organic production represents a path towards the transition of sustainable food production, as they include family and non-family farmers.